Calcium Profile of Chronic Kidney Disease Patients Undergoing Hemodialysis - Ahmad Yani; Desiana Wahyu Kuswardani; Citra Trisna; Venny Patricia (Journal of Noncommunicable Diseases Prevention and Control, 2024)
Chronic kidney disease (CKD) is a condition of progressive kidney deterioration, which is characterized by a decrease in the estimated glomerular filtration rate that lasts for more than three months. One of the therapies needed to maintain the quality of life of CKD sufferers is hemodialysis. One of the functions of hemodialysis is to regulate electrolyte levels in the blood, including calcium. Low calcium levels in the blood (hypocalcemia) can trigger the release of calcium minerals from the bones, which ultimately makes the bones brittle. So, it is essential to monitor the blood calcium levels of CKD sufferers so as not to worsen the sufferer's condition. This study used secondary data, and the research instrument used in this research was the patient's medical record. Sampling was carried out using the purposive sampling method. The inclusion criteria set were patients with CKD who underwent hemodialysis and had complete medical record data, including age, gender, length of time undergoing hemodialysis, and examination data in the form of blood calcium levels. The data included in this study came from 68 patients with CKD who underwent hemodialysis and had their blood calcium levels checked. Based on the research results, the prevalence of CKD was more significant in men (58.82%), and as many as 92.65% of the total respondents experienced hypocalcemia. Cases of hypocalcemia occurred more frequently in male patients (52.94%), in the 46-65 year age group (55.88%), and in patients who had undergone hemodialysis for 4-12 months (45.59%). Hypocalcemia sufferers need to pay attention to their nutritional intake to keep their blood calcium levels at a safe level.